The effects of protracted conflict and displacement on citizen engagement in Northern Uganda. Issue 1 (2nd January 2016) - Oosterom, Marjoke A.
Abstract: The Acholi region of Uganda was deeply affected by the war between the Lord's Resistance Army and the Government of Uganda from the late 1980s to 2006. This article presents qualitative case-study research of how citizen engagement evolved during the conflict and period of internal displacement, analysing the mechanisms through which violent conflict affected the sense and practice of citizenship. The findings show that the securitisation of local institutions and the militarisation of the public sphere limited the opportunity for learning the practice of citizenship. In the post-conflict situation, perceptions and behaviours that developed during the conflict period persist among the Acholi. Finally, the experience of protracted conflict has a negative impact on a sense of citizenship, which weakens the confidence of the Acholi people to engage with the state. With practices of citizenship limited by inexperience and a sense of citizenship that is characterised by alienation, the Acholi find it difficult to hold state actors to account. This demonstrates the need for a clear understanding of the continued fragility of citizenship after violent conflict.